The Effect of Solar-Wind Turbulence on Magnetospheric Activity - D’Amicis, R.; Telloni, D.; Bruno, R. (Frontiers in Physics, 2020)
The solar wind is a highly turbulent medium exhibiting scalings of the fluctuations ranging over several decades of scales from the correlation length down to proton and electron gyroradii, thus suggesting a self-similar nature for these fluctuations. During its journey, the solar wind encounters the region of space surrounding Earth dominated by the geomagnetic field which is called magnetosphere. The latter is exposed to the continuous buffeting of the solar wind which determines its characteristic comet-like shape. The solar wind and the magnetosphere interact continously, thus constituting a coupled system, since perturbations in the interplanetary medium cause geomagnetic disturbances. However, strong variations in the geomagnetic field occur even in absence of large solar perturbations. In this case, a major role is attributed to solar wind turbulence as a driver of geomagnetic activity especially at high latitudes. In this review, we report about the state-of-art related to this topic. Since the solar wind and the magnetosphere are both high Reynolds number plasmas, both follow a scale-invariant dynamics and are in a state far from equilibrium. Moreover, the geomagnetic response, although closely related to the changes of the interplanetary magnetic field condition, is also strongly affected by the intrinsic dynamics of the magnetosphere generated by geomagnetic field variations caused by the internal conditions.